Comparison of Antioxidant Activity of Mistletoe Mango Leaves Extract (Dendrophtoe pentandra (L.) Miq) Using Ethanol Solution and Methanol Solution Based on DPPH Method - Silvia, Putri Azizatul; Sjakoer, Nour Athiroh Abdoes; Mubarakati, Nurul Jadid (JSMARTech, 2024)
Indonesians have been utilising plants as traditional raw materials, especially herbal plants, since the time of the struggle until the current independence. Mistletoe mango which belongs to the Loranthaceae family, leaves of mistletoe mango is considered a medicinal plant. Phytochemical analysis shows that these plants contain a number of secondary metabolites, such as flavonoids, saponins, tannins, alkaloids, glycosides, and inulin. Antioxidants are compounds that can prevent oxidation reactions by binding free radicals and highly reactive molecules. The DPPH method is a simple, easy, rapid and sensitive antioxidant activity test method that uses only a small sample. The aim was to determine the comparison of the antioxidant activity of mistletoe mango leaves extract (Dendrophthoe pentandra (L) Miq) with ethanol and methanol solvents, as well as analyzing the 50% inhibitin of DPPH. The results showed that the antioxidant activity of mistletoe mango leaves extract using ethanol solvent was 15,286 ppm, while using methanol solvent was 93,456 ppm. It was concluded that antioxidant activity showed a very strong category and there was a significant difference.